Toleransi Beragama dalam QS. Al-Mumtahanah 8-9 Tipologi Muhammad Mutawalli As-Sya’rawy dalam Tafsir As-Sya’rawy - Rizqiutami, Sellindra; Rambe, Uqbatul Khoir; Ekowati, Endang (ANWARUL, 2023)
The problem raised in this research is how religious tolerance is found in the interpretation of the QS. Al-Mumlahanah 8-9 according to Muhammad Mutawalli as-Sya'rawy's typology in as-Sya'rawy's interpretation. The aim of this research is to find out how religious tolerance is in QS. Al-Mumlahanah 8-9 As-Sya'rawy's perspective and knowing the typology of religion adopted by Muhammad Mutawalli As-Sya'rawy in the interpretation of the QS. Al-Mumlahanah 8-9 regarding religious tolerance. This type of research is qualitative with a library research method by collecting various literature related to the object of discussion being studied and then analyzing it using tahlili interpretation analysis tools. Sources of data in this study consisted of primary data and secondary data. From this study it was found that religious tolerance from the as-Sya'rawy perspective in QS. al-Mumtahanah 8-9 namely, first, there is no prohibition to do good to fellow human beings, even though they have different religions. Second, the ability to give to each other even though they have different religions. Third, it is permissible to please the hearts of fellow religious adherents. Fourth, the ability to lighten one another's burdens even though they are of different religions and to maintain the dignity and worth of one another. Fifth, maintain an attitude of tolerance as long as you don't fight, make enemies or expel you from your hometown and are prohibited from collaborating with groups that behave like that. Meanwhile, the religious typology adopted by as-Sya'rawy in interpreting QS. Al-Mumlahanah 8-9 is a typology of pluralism. This pluralist typology is a religious view that is suitable for people who live amidst diversity, such as as-Sya'rawy, who also lives in a multicultural environment consisting of various religions and races in Egypt.